How do young men want to receive information about fertility? Young men's attitudes towards a fertility campaign targeting men in Copenhagen, Denmark. Issue 3 (27th July 2021) - Berthelsen, A S N; Gamby, A L N; Christensen, U; Schmidt, L; Koert, E
Abstract: STUDY QUESTION: What are young men's attitudes towards the Danish fertility campaign 'How's your sperm?' and how do they want to receive fertility information in the future? SUMMARY ANSWER: The young men found that the campaign had limited impact because it was not relevant to their current life situation and they believed general fertility awareness should be a mandatory part of education, while more targeted information would be helpful through web-based venues when it was more relevant to their lives (e.g. when ready to have children). WHAT IS KNOWN ALREADY: It is estimated that 16–26% of the Danish population who want children will experience infertility at some point in their lives. In Denmark, 25% of young healthy men have decreased sperm quality, and 20% of 50-year-old men are childless. Men play an important role in the fertility decision-making of couples, thus, it is important to target men and ensure that they have sufficient fertility knowledge. However, fertility awareness is limited among men and there have been few fertility awareness initiatives targeting men. In October 2018, the Municipality of Copenhagen launched the campaign 'How's your sperm?' as a tool to increase fertility knowledge among men. To identify potential barriers for the effect of fertility campaigns targeting men, evaluations of such campaigns are needed. STUDY DESIGN, SIZE, DURATION: This study was a cross-sectional, qualitative study of six focus groups including a total of 27 currently childless young men from the Capital Region of Copenhagen, Denmark. Data collection took place between April and October 2019. PARTICIPANTS/MATERIALS, SETTING, METHODS: The interviewed young men were currently childless and were all residents in the Capital Region of Copenhagen. They were between 23 and 32 years old with an average age of 26 years, and almost all were university students or had a university degree. The focus group discussions were audiotaped, anonymized and transcribed in full. Data were analyzed using qualitative content analysis. MAIN RESULTS AND THE ROLE OF CHANCE: Overall, the campaign had limited influence on the young men because they believed the campaign was not relevant to their current life situation. Furthermore, the young men were confused about the aim and message of the campaign, as they thought it encouraged them to have their sperm quality tested. The young men also criticized the campaign for making a link between sperm quality and masculinity. They recognized the importance of knowledge about reproductive health but they wanted access to accurate information about fertility and risk factors for infertility. According to the young men, future initiatives should prioritize clear communication of accurate, reliable and understandable fertility information in web-based venues. In addition, the young men suggested that general fertility information should be a mandatory part of the (sexual) education curriculum in primary and secondary schools. LIMITATIONS, REASONS FOR CAUTIONS: Participants were young and highly educated; thus the findings cannot be generalized to all men of a similar age group or to men at older ages. WIDER IMPLICATIONS OF THE FINDINGS: Different strategies that are relevant to the lifespan are needed to increase fertility awareness in the male population. The young men's responses underscored that any fertility awareness strategy or campaign must convey respect for the individual's autonomy. The findings highlight that how information is communicated and the quality or type of information that is disseminated are both important in acceptability by target users. STUDY FUNDING/COMPETING INTEREST(S): No funding was received for this study. No conflicts were declared for all authors. TRIAL REGISTRATION NUMBER: N/A.